THE EFFECTIVENESS OF ERGONOMICS TECHNIQUES ON THE ABILITY TO OVERCOME MUSCULOSKELETAL DISORDER (MsDs) COMPLAINTS AMONG TAILORS IN BENGKULU CITY AND JAKARTA CITY 2019 - Sri Mulyati; Kuat Prabowo; Deri Kermelita (Poltekkes Kemenkes Bengkulu, 2022)
Ergonomics is essential to study because it can avoid fatigue and muscle injuries affecting employee performance. One of the diseases caused by ergonomics is the complaint of MsDs. There is an effect of the ergonomic technique on the ability to reduce MsDs complaints in tailors in Bengkulu and Jakarta. This research to know the ergonomic of the sewers and to identify the complains MsDs before and after intervention and the influence of the true ergonomic intervention toward the compalains of MsDs. The research uses a quantitative survey design with a quasi-experimental approach to non-randomized control group pre-test-post-testing (training intervention group respondents using a module on ergonomic techniques when sewing) and observing ergonomic practices when sewing. Data analysis used univariate and bivariate. Research results in ergonomic variables: Bengkulu City before treatment mean 7.55 after treatment 12.05. The city of Jakarta before the treatment means 7.50. After treatment, the mean is 11.0. MsDs complaint variable: Bengkulu city before treatment mean 63.8 and after treatment mean 45.3. The city of Jakarta before treatment means 64.82 after treatment means 45.3. Suggestions are expected that the tailors in the treatment group use a module that the tailor has received to be a guide in sewing work to minimize MsDs complaints.